ANALISIS PENGARUH DIVERSITAS GENDER, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Lisaime Lisaime; Dewi Sri (Catholic University Musi Charitas, 2018)
Research on the analysis of the effect of gender diversity, institutional ownership, and firm size on financial performance using the population of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Sampling was done by purposive sampling method as many as 65 companies. This study wants to see the effect of gender diversity, institutional ownership, and firm size on financial performance. Based on the results of testing the hypothesis obtained that Ha is accepted, namely institutional ownership has a positive effect on financial performance. While the hypothesis for the gender of the board of directors, the gender of the board of directors and the size of the company shows that H0 is accepted, namely the gender of the board of directors, the gender of the board of directors, and the size of the company does not have a positive effect on financial performance